Maturity, physical ability, technical skill and coaches` perception of semi-elite adolescent australian footballers - Cripps, A. J.; Hopper, L.; Joyce, C. (Pediatric Exercise Science, 2016)
Purpose: To confirm the effect of maturational differences on anthropometric and physical testing and explore the effect of maturation on technical skill and coaches` perceptions of skill in adolescent Australian footballers. Methods: Athletes were recruited from a semielite under 16 competition (n = 94, age 15.7 ± 0.3 years) and completed anthropometric, physical, and technical skill tests. Coaches from each team provided subjective ratings of athletes` technical skills. Maturation groups were derived from years from peak height velocity estimates, with classifications either later, average or earlier maturing. Results: Effect size comparisons revealed very large to moderate effects between groups for anthropometric measures and performance in sprint and jump tasks. Small to moderate effects were reported between groups for coaches` perceptions of skill, with the earlier maturing group perceived to have better overall technical skills, marking and ball winning abilities. Small to trivial effects were reported for performance in the technical skill tests. Conclusion: Despite no differences in skill tests, earlier maturing athletes may be afforded significant selection and competition advantages due to advanced physical capacities and coaches` perceptions of skill.